Targeting the ubiquitin pathway in lymphoid malignancies - Li, Boheng; Eichhorn, Pieter; Chng, Wee-Joo (Elsevier, 2024)
Ubiquitination and related cellular processes control a variety of aspects in human cell biology, and defects in these processes contribute to multiple illnesses. In recent decades, our knowledge about the pathological role of ubiquitination in lymphoid cancers and therapeutic strategies to target the modified ubiquitination system has evolved tremendously. Here we review the altered signalling mechanisms mediated by the aberrant expression of cancer-associated E2s/E3s and deubiquitinating enzymes (DUBs), which result in the hyperactivation of oncoproteins or the frequently allied downregulation of tumour suppressors. We discuss recent highlights pertaining to the several different therapeutic interventions which are currently being evaluated to effectively block abnormal ubiquitin-proteasome pathway and the use of heterobifunctional molecules which recruit the ubiquitination system to degrade or stabilize non-cognate substrates. This review aids in comprehension of ubiquitination aberrance in lymphoid cancers and current targeting strategies and elicits further investigations to deeply understand the link between cellular ubiquitination and lymphoid pathogenesis as well as to ameliorate corresponding treatment interventions.